2009
DOI: 10.1016/j.euroneuro.2008.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state methadone blocks cocaine seeking and cocaine-induced gene expression alterations in the rat brain

Abstract: To elucidate the effects of steady-state methadone exposure on responding to cocaine conditioned stimuli and on cocaine-induced alterations in central opioid, hypocretin/orexin, and D2 receptor systems, male Sprague-Dawley rats received intravenous infusions of 1 mg/kg/inf cocaine paired with an audiovisual stimulus over three days of conditioning. Then, mini pumps releasing vehicle or 30 mg/kg/day methadone were implanted (SC), and lever pressing for the stimulus was assessed in the absence of cocaine and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 86 publications
(101 reference statements)
5
28
0
Order By: Relevance
“…Both reduced availability of D2 receptor binding and decreased D2 gene expression in the striatum have been consistently associated with heroin cravings in humans [e.g., 38, 39] and cocaine seeking in animals [e.g., 25, 26]. In the present study, we observed a down-regulation of CPu D2 mRNA levels in the H-RI rats.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Both reduced availability of D2 receptor binding and decreased D2 gene expression in the striatum have been consistently associated with heroin cravings in humans [e.g., 38, 39] and cocaine seeking in animals [e.g., 25, 26]. In the present study, we observed a down-regulation of CPu D2 mRNA levels in the H-RI rats.…”
Section: Discussionsupporting
confidence: 66%
“…Nine days after heroin self-administration, specific brain regions were collected to quantify AVP, POMC and orexin gene expressions, and the alterations were analyzed in the H-RI and L-RI groups. Because availability of dopamine D2 receptor (D2) binding and D2 gene expression in the striatum have been associated with cocaine seeking [25, 26], we also determined if the changes in striatal D2 expression, as well as in the stress hormones (ACTH, corticosterone and prolactin), were correlated with vulnerability to stress-induced heroin-seeking.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Davis & Smith (1976) paired a stimulus with drug delivery and showed that making stimulus-presentation response-contingent maintained responding (see also Leri et al 2009). Thus, drug-paired stimuli can at least temporarily maintain behavior as a result of Pavlovian learning.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the EOS has been implicated in drug-seeking behavior (Leri, Zhou, Goddard, Cummins, & Kreek, 2006;Leri et al, 2009), craving, and relapse (Ghitza et al, 2010;Gorelick et al, 2005) in cocaine addiction. Thus, alterations in the EOS, especially the expression of the KOR and MOR, can potentially exacerbate the risk of cocaine addiction.…”
Section: Cocaine and Hiv-1mentioning
confidence: 99%